2017
DOI: 10.1177/1046496417724209
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organizing Into Winning Teams: Understanding the Mechanisms That Drive Successful Collaborations

Abstract: Contemporary teams are self-assembling with increasing frequency, meaning the component members are choosing to join forces with some degree of agency rather than being assigned to work with one another. However, the majority of the teams literature up until this point has focused on randomly assigned or staffed teams. Thus, the purpose of the current study was to investigate how people do form into teams and how people should form into teams. Specifically, we utilized a sample of digital traces from a massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 103 publications
2
22
0
Order By: Relevance
“…Assembling on an ad hoc basis can be seen as associated with the concept of interpersonal attraction, where people develop an attitudinal positivity for one another (Huston & Levinger, 1978). This attraction is the result of the members' relatedness, which highlights the importance of relative (e.g., similarity), rather than absolute attributes (e.g., status), as well as the significance of relational attraction (familiarity) (Wax et al, 2017). These factors are conducive to shared mental models, as in and of themselves presuppose a common ground, and as our findings indicated, shared mental models support quality communication and help members identify with the shared values of the virtual team, which ultimately lead to perceived proximity.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Assembling on an ad hoc basis can be seen as associated with the concept of interpersonal attraction, where people develop an attitudinal positivity for one another (Huston & Levinger, 1978). This attraction is the result of the members' relatedness, which highlights the importance of relative (e.g., similarity), rather than absolute attributes (e.g., status), as well as the significance of relational attraction (familiarity) (Wax et al, 2017). These factors are conducive to shared mental models, as in and of themselves presuppose a common ground, and as our findings indicated, shared mental models support quality communication and help members identify with the shared values of the virtual team, which ultimately lead to perceived proximity.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Geographically dispersed team environments present a number of issues that negatively influence team performance. These issues range from lack of personal ties to collaboration-related problems to leadership challenges (Gilson et al, 2015; Ortiz de Guinea, Webster, & Staples, 2012; Wax, DeChurch, & Contractor, 2017). Greater team dispersion presents additional hindrances to team performance because distance, time, culture, and multiple other boundaries restrict the opportunities for quality interactions and hinder team members’ abilities to cultivate interpersonal relationships.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Research has been conducted on a Massively Multiplayer Online Role Playing Games (MMORPG), Dragon Nest [33], which revealed that self-assembled teams form via three mechanisms: homophily, familiarity, and proximity; the authors show that successful and unsuccessful teams were homogeneous in terms of different characteristics, but successful teams are more often formed based on friendship than those unsuccessful teams.…”
Section: B Social Ties In Games and Virtual Teamsmentioning
confidence: 99%